Dynamics of timber market integration in Sweden - Jaunky, Vishal; Lundmark, R. (2015)
© 2015 by the authors.This paper addresses the performance of the timber markets (Scots pine, Pinus silvestris L. and Norway spruce, Picea abies (L.) Karst.) by evaluating the order of market integration in three Swedish regions (Central, Northern, and Southern). Quarterly data of delivery prices are employed over the period 1999Q1-2012Q4. Various unit root and cointegration tests have been computed. The results indicate that the variables are integrated of first order and co-integrated, especially after controlling for structural breaks. This supports the law-of-one-price hypothesis (LOP). However, the effects of structural shocks on forestry are arguably significant and these are controlled for while performing a vector error-correction mechanism (VECM)-based Granger-causality test. Bi-directional causality between the Northern and central markets is uncovered in the short-run. In the long-run, a similar causal effect is detected between Northern and Southern markets while the central market emerges as the price leader. Further investigation is carried out using variance decompositions and impulse response functions and these approaches also tend to confirm the existence of a single market well, as price interdependence between markets.